Bilawhar wa Buyūdhasf - Tabrīzī, Niẓām (Miras Maktoob, ISBN: 9789004365452., 2020)
Bilawhar and Būdhāsaf are the main characters of an ancient Arabic work called Bilawhar wa-Būdhāsaf , a text whose core narrative derived from the biography of Gautama Buddha, the founder of Buddhism. The original Sanskrit text on which it was based was translated into Middle Persian and from there into Arabic, besides Old Turkish and New Persian. It is from this lost ancient Arabic translation that later versions, adaptations or summaries derive, whether in Arabic, Persian, Georgian, Hebrew, or Greek. The Persian work published in this volume is Niẓām Tabrīzī's (fl. late 8th/14th cent.) summary of an anonymous Persian translation of an equally anonymous Arabic commentary on Bilawhar wa-Būdhasaf , both lost. As such, it provides new material for further study into the history of transmission of this text, both from a philological point of view and as a complex narrative issuing from a progressive intermixture of elements from different times and cultures.